Differential responsiveness of cerebellar Purkinje neurons to GABA and benzodiazepine receptor ligands in an animal model of hepatic encephalopathy - Basile, AS (J Neurosci, 1988)
The role of the GABA-benzodiazepine receptor complex in the pathogenesis of hepatic encephalopathy was investigated by recording the electrophysiological responses of single cerebellar Purkinje neurons from rabbits with hepatic encephalopathy due to galactosamine- induced fulminant hepatic failure. Both the GABAmimetic muscimol and the benzodiazepine receptor agonist flunitrazepam were 3–4 times more potent in depressing the spontaneous activity of Purkinje neurons from rabbits with hepatic encephalopathy than from control animals. Furthermore, qualitatively different responses of Purkinje neurons to benzodiazepine receptor antagonists (Ro 15–1788 and Ro 14–7437) were found in controls and rabbits with hepatic encephalopathy. These compounds markedly excited Purkinje neurons from rabbits with hepatic encephalopathy, but had either no effect (Ro 14–7437) or partially suppressed (Ro 15–1788) the spontaneous activity of neurons from control animals. In addition, incubation of Purkinje neurons from rabbits with hepatic encephalopathy with subthreshold concentrations of Ro 14–7437 reduced their sensitivity to muscimol, whereas treatment of control neurons with Ro 14–7437 had no effect on their sensitivity to muscimol. Finally, Purkinje neurons from hepatic encephalopathy and control rabbits displayed no difference in sensitivity to the depressant actions of the alpha-adrenoceptor agonist phenylephrine. These findings demonstrate a differential responsiveness of Purkinje neurons from an animal model of hepatic encephalopathy to ligands that interact with the GABA-benzodiazepine receptor complex. Furthermore, the observations made in this experimental model are consistent with the involvement of the GABA-benzodiazepine receptor complex in mediating hepatic encephalopathy, and provide a potential explanation for the reported efficacy of benzodiazepine receptor antagonists in ameliorating this syndrome.